Bullying in gifted and talented children: A systematic review - Sri Febriana; Syafrimen Syafril; Cahniyo Wijaya Kuswanto (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
The objective of this study was to carry out a systematic review of the research works that have analyzed bullying in gifted and talented children. The search was conducted in psychology and education databases (Scopus), considering works from the past 14 years (2009-2022). The research method used is the systematic literature review (SLR) method; the data is analyzed qualitatively, referring to the Milles and Huberman model, which includes data reduction, data presentation, and data validation. The search string in this study is "bullying," AND "gifted," OR "talented," OR "children." The articles that have been selected are then mapped and codified with Nvivo 12 Pro. The results showed that gifted and talented children in early childhood institutions are more likely to be victims of bullying by their peers due to their unique characteristics and superior cognitive functions. Bullying behavior commonly experienced by gifted children takes the form of insults referring to their intelligence, comments about their appearance, or academic qualifications. Therefore, teachers play an essential role in creating a positive environment, rewarding high academic achievement, and conducting early identification. This study highlights the educational stakeholders' need to provide training or specific actions to the managers of early childhood institutions related to the prevention of bullying in gifted and talented children.